THE EFFECTIVENESS OF SHORT STORIES IN READING SKILL - Novasyari, Ressy; Fauziah, Debby (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2023)
ABSTRACT Some researchers stated that many problems and difficulties faced by students in learning a foreign languages likes teacher centered, boring teaching and learning material used in the classroom, low motivation of learning. The purpose of this article is to describe the effectiveness of short stories in reading skill. Learning English through short stories can make students to be creative and affect learners’ attentions effectively not only in reading skill but also another skills such as listening, speaking and writing. Using short stories is recommended in learning a foreign language because teachers can teach literary works, cultural, and higher –order thinking and many aspects of language. ABSTRAK Beberapa peneliti mengatakan bahwa banyak permasalahan dan kesulitan yang dihadapi oleh siswa dalam belajar bahasa asing seperti guru yang menjadi pusat belajar, materi yang di ajarkan membosankan, kurangnya motivasi dalam belajar. Tujuan dari artikel ini adalah menjelaskan efektivitas cerita pendek dalam kemampuan membaca. Belajar bahasa Inggris melalui cerita pendek bisa membuat siswa menjadi kreatif dan memberikan pengaruh perhatian yang efektif tidak hanya dalam kemmapuan membaca tetapi juga kemampuan yang lain seperti mendengar, berbicara dan menulis. Menggunakan cerita pendek di rekomendasikan dalam belajar bahasa asing karena guru bisa mengajar literasi, budaya, dan berpikir tinggi dan banyak aspek bahasa lainnya.